Study of Methods, Mechanisms and perspectives for the synthesis and applications of Vinyl sulfone compounds (with reference to organic synthesis and Pharmaceutical Chemistry) (International Journal of Food and Nutritional Sciences, 2022)
Vinyl sulfones have grown to be useful catalysts and reagents in organic synthesis, as well as bendy building blocks. Their employment in the production of various molecular frameworks, which include natural products, drug treatments, heterocycles, and functionalized molecules, is made feasible by way of their special reactivity, adaptability, and stability. They can also take part in loads of approaches, along with Michael additions, cycloadditions, Diels-Alder reactions, oxidations, discounts, and the creation of C-C/C-heteroatom bonds, in addition to their electrophilicity, Lewis acidity, and redox traits. Vinyl sulfones have a twin role in the production of complicated compounds and practical substances by facilitating efficient synthesis and functionalization. Beyond their synthetic skill, the organic hobby, pharmacokinetic traits, and structural style of vinyl sulfones display top-notch prospects as therapeutic candidates for more than a few disorders. Examples are Recilisib for irritation, Rigosertib and BAY eleven-7085 for cancer, and K11777 and Rigosertib for parasitic illnesses. Vinyl sulfones also provide beneficial scaffolding for drug discovery and improvement, facilitating short searches of the chemical space and the powerful identification of viable healing applicants. In the future, vinyl sulfone synthesis might be further advanced with the aid of more effective and environmentally pleasant synthetic strategies, which include non-stop glide techniques, enzyme-catalysed techniques, photochemical techniques, and electrochemistry. Furthermore, the variety of reachable vinyl sulfone derivatives may be multiplied with the aid of investigating enantioselective strategies such as the use of chiral catalysts, asymmetric organocatalysis, and biocatalysis using designed enzymes.